Interview with Dr. Keshab Man Shakya, Hon’ble Minister for Science, Technology and Environment - Thanju, Jeewan P. (Hydro Nepal: Journal of Water, Energy and Environment, 2013)
Not available. Hydro Nepal; Journal of Water, Energy and Environment Issue No. 12, January 2013 Page: 87-88 DOI: http://dx.doi.org/10.3126/hn.v12i0.9040 Uploaded date: 7 Nov., 2013